Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1096/fj.14-262154
|View full text |Cite
|
Sign up to set email alerts
|

Serum C1q as a novel biomarker of sarcopenia in older adults

Abstract: Aging-induced elevation in C1q secretion activates the Wnt signaling pathway in muscles, leading to the development of muscle fibrosis. However, the association between serum C1q level and muscle mass and strength remains unclear in humans. The aim of the study was to elucidate whether serum C1q level is associated with aging- and resistance training-induced changes in muscle mass and strength. First, in a cross-sectional study, we investigated the association between serum C1q level and muscle mass and streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 30 publications
5
38
2
Order By: Relevance
“…Together, our data indicate that C1q significantly amplifies peritoneal fibrosis by promoting a type 2 macrophage phenotype driven by lactate and dependent on HIF1α. These results are consistent with human studies in which C1q is strongly associated with increased fibrosis of skeletal muscle (24). …”
supporting
confidence: 92%
“…Together, our data indicate that C1q significantly amplifies peritoneal fibrosis by promoting a type 2 macrophage phenotype driven by lactate and dependent on HIF1α. These results are consistent with human studies in which C1q is strongly associated with increased fibrosis of skeletal muscle (24). …”
supporting
confidence: 92%
“…Sarcopenia is well known to be linked to a low degree of physical activity, and it has been shown that exercise, especially resistance training, increases (Watanabe et al 2015).…”
Section: Behavior-mediated Pathwaysmentioning
confidence: 99%
“…In the elderly population, plasma pro-inflammatory cytokines, IL-6 and TNF-α, and the acute phase C-reactive protein (CRP) are chronically elevated. When young (<40 years) and aged (60–81 years) populations were compared in a series of age-related parameters, including muscle mass, plasma C1q, as well as plasma IL-6, TNF-α, and CRP, the young population had clearly lower plasma C1q (80.5 µg/ml) than the aged population (161 µg/ml) (51). Interestingly, after 12 weeks of supervised resistance training intervention, plasma C1q in the elderly group decreased substantially (89.3 µg/ml) with muscle mass being significantly increased, revealing an inverse correlation between plasma C1q level and muscle mass (51).…”
Section: Plasma C1q Accumulation Is Associated With Accelerated Agingmentioning
confidence: 99%
“…When young (<40 years) and aged (60–81 years) populations were compared in a series of age-related parameters, including muscle mass, plasma C1q, as well as plasma IL-6, TNF-α, and CRP, the young population had clearly lower plasma C1q (80.5 µg/ml) than the aged population (161 µg/ml) (51). Interestingly, after 12 weeks of supervised resistance training intervention, plasma C1q in the elderly group decreased substantially (89.3 µg/ml) with muscle mass being significantly increased, revealing an inverse correlation between plasma C1q level and muscle mass (51). The cause for plasma C1q accumulation in the elderly group and its reduction after training is unclear in this study and a causal relationship between plasma C1q and muscle mass was also not established (51).…”
Section: Plasma C1q Accumulation Is Associated With Accelerated Agingmentioning
confidence: 99%